THE CORRELATION BETWEEN SELFREGULATION WITH DEVIATION BEHAVIOR IN PRISONERS OF SEXUAL VIOLENCE IN LEMBAGA PEMASYARAKATAN KLAS II A KARAWANG - Mubina, Nuram; Muharsih, Lania; Saefudin, Nugraha (International Journal of Psychosocial Rehabilitation, 2020)
Each individual has self-regulation ability that can be used to regulate and detain himself from deviant behavior or deviation, but this ability is not automatically activated, if the active self- regulation or high ability of individuals will tend to behave normally according to applicable norms and laws, but if the ability individual self-regulation has not been active or low, then the individual’s deviation behavior will tend to be high, so that individuals have the potential to commit crimes, one of which is sexual crime. This study aims to determine the relationship between deviation behavior and self-regulation in prisoners of perpetrators of sexual violence Lapas Klas II A Karawang. The hypothesis of this study shows that there is a negative relationship between deviation behavior and the self-regulation of prisoners of sexual crimes. The subject of this study was 79 convicted perpetrators of sexual violence Lapas Klas II A Karawang. This study uses a quantitative correlational method with a scale of deviation behavior and a self-regulation scale as a data collection tool. The behavioral deviation scale consists of 22 items with a reliability coefficient of 0.797. While the self-regulation scale consists of 35 items with a reliability coefficient of 0.908. The results of data analysis using Product Moment Correlation indicate that there is a negative relationship between deviation behavior and self-regulation in prisoners of sexual violence Lapas Klas II A Karawang of -0.598 with a significance of 0.00.